Strategy Of The Local Government Of Mamasa Regency In Preventing Religious Conflicts To Realize National Security - Julianto Exel Allolayuk; Kusuma, Kusuma; Achmed Sukendro; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2024)
Managing diversity based on local democracy is a preventive step to prevent prolonged conflicts toward social reintegration. Religious segmentation is used as a way to unravel the political conflicts that previously echoed in this area. Efforts to carry out the representation of religious identity (Islamic-Christian) in each Regional Election event are used as a new political format to minimize the tension of identity politics that can erode the spirit of community togetherness. Representation politics is then manifested in the form of pairs of candidates to occupy the position of regional head until the last twenty years have been institutions that have the ability to maintain unity and unity. This research uses a qualitative approach. For data collection techniques, researchers conduct interviews, observation, and documentation procedures. The theories and concepts used in this study include strategy theory, peace theory, conflict theory, conflict prevention concept, Conflict early Warning and Early Response System (CEWERS) concept, and state defense concept. Based on the results of the study, it can be understood that overall, conflict management carried out by the government, both the central government and local governments, is very poor. Efforts to resolve conflicts only occur at the elite level and do not include people who suffer more and lose more due to conflict. An elitist resolution will only meet the interests and demands of the elite. The demands of the masses that should also be accommodated are ignored. As a form of strategic steps of the local government of Mamasa Regency in preventing conflicts in the administration of government and its relationship with the roots of religious conflicts in Mamasa Regency, some of the descriptions of the steps taken include the Education and Socialization Approach, Increasing the Role of the Religious Harmony Forum (FKUB), Strengthening the Economy and Social Welfare, Fair and Transparent Law Enforcement, and Inclusive Infrastructure and Public Facilities Development.